Appropriate technology for windrow composting of oil palm empty fruit bunches - Mohamad Shukery, Mohamad Firdza; Suryanto, Hadi; Yahya, Azmi (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Composting of oil palm empty fruit bunches (EFB) under indoor windrow composting method with a newly developed compost turning machine was studied. The self-propelled compost turning machine was developed to mix and aerate 16 tons of pre-pressed and pre-shredded EFB in four longitudinal heaps having size of 2.50 meter width, 1.50 meter height and 12.0 meter length indoor with concrete flooring. Field performances of the compost turning machine and physical characteristics of the composted EFB were monitored throughout the 12 weeks of composting period. The average mass throughput capacity of the turning machine and total mass production of composting plot were found to be 84.83 ton/hr and 47.29 ton/hr, respectively. The average C/N ratios of the composted EFB in all the heaps had reduced from 66.30 to 29.34 (55.6% reduction) and the average heap volume had been reduced to 47.7% at the week 12th of composting period. Composting of EFB with this employed windrow composting system was able to convert large volume of bio-waste into valuable bio-compost fertilizer. Consequently, the proposed system helps in utilizing waste that produced from oil palm mill and reducing fertilizer cost that is a burden to the oil palm plantation.